(untitled) (Journal of Forestry, 2024)
The paper analyzes measures necessary for fire protection and the associated costs related to the period before, during and after the fire. It is obvious that costs increase in conditions of frequent fires. Therefore, it is necessary to intensify preventive measures and works that can reduce the risk of fires in open space and affect the reduction of the area affected by fire. This paper offers a list of preventive measures that should be implemented during every fire season for the sake of the effectiveness of the system of firefighting activities. Namely, their effectiveness can directly affect the reduction of total costs when extinguishing fires, because less consumption and use of resources in firefighting is required. The costs are high when the firefighting intervention of ground forces is taken into account, which is increased by the participation of firefighting aircraft. The key period in which preventive measures should be successfully implemented is during the fire season from June 1 to September 30. Also, any investment in preventive measures in forestry reduces the costs of rehabilitating fire areas and restoring forests and forest land.